Investigating Figurative Language Used in Katy Perry’s Song Lyrics - Azhari Zama; Hendra Heriansyah; Nurul Inayah (Research in English and Education Journal, 2019)
This study aimed at investigating the types of figurative language found in Katy Perry’s song lyrics. It also tried to find out the functions of figurative language in these songs. A descriptive qualitative was undertaken to investigate the research questions in this study. Abrams and Harpham’s theory (2005) used to analyze the data related to the types of figurative language. While, Jakobson’s theory (1995, as cited in Tribus, 2017) utilized to analyze the functions from the types figurative language found in the song lyrics.  The results of the study showed that there are some types of figurative language used in Katy Perry’s song lyrics such as simile, metaphor, hyperbole, alliteration, etc. Simile and repetition are the two most frequent types of figurative language found in these songs. Meanwhile, there are two functions of figurative language discovered through the song lyrics namely conative and poetic. The poetic function is the most one used in the song lyrics. In conclusion, the figurative language is a commonly matter used in the literature area.